2022
DOI: 10.3390/su14063590
|View full text |Cite
|
Sign up to set email alerts
|

Trade Openness and Environmental Policy Stringency: Quantile Evidence

Abstract: The intensively debated issue of whether trade globalization leads to a race (climb) to the bottom (top) such that environmental policy stringency is loosened (strengthened) is still far from being uncontroversial. This paper provides new empirical evidence from the standpoint of the North (advanced) countries using both the generalized methods of moment (GMM) and GMM quantile estimators for dynamic panel data models. It first investigates the importance of trade partners and finds, in a sample of OECD countri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…On the other hand, one-way causality between environmental stringency policy and carbon dioxide emissions is found in China, Canada, and France (Sezgin et al, 2021). Kim and Lin (2022) examined the environmental stringency policy in OECD economies. It is found that medium stringency fades the environmental stringency policy while emphasizing the environmental stringency policy with low and high stringency.…”
Section: Literature Review Fdi Energy and Environmentmentioning
confidence: 99%
“…On the other hand, one-way causality between environmental stringency policy and carbon dioxide emissions is found in China, Canada, and France (Sezgin et al, 2021). Kim and Lin (2022) examined the environmental stringency policy in OECD economies. It is found that medium stringency fades the environmental stringency policy while emphasizing the environmental stringency policy with low and high stringency.…”
Section: Literature Review Fdi Energy and Environmentmentioning
confidence: 99%
“…The performance metric is not restricted to economic growth only but also cuts across issues relating to poverty alleviation, price stability, and reduction in unemployment (Figueiredo, & Lima, 2022;Sakyi et al, 2017). Consequently, developing economies have resorted to trading policies as tools that can spur development objectives such as creating employment and alleviating poverty Ngouhouo and Nchofoung, 2021;Kim and Lin, 2022). The renewed interest in trade-led growth has been accompanied by a tremendous increase in trade volume globally.…”
Section: Introductionmentioning
confidence: 99%